State authority and local power in Southern Philippines, 1900-1972 - Abinales, Patricio N. (Ann Arbor, MI ProQuest Dissertations & Theses Global, 1997)
"The southern Philippine island of Mindanao became the battleground of two major armed rebellions in the 1970s: one sought to create a separate Muslim state and the other, a communist insurgency, aspired to overthrow the Philippine state. Standard explanations of these rebellions point to the explosive combination of "historic" ethnic disputes, massive demographic changes accompanying the closing of the frontier, rising class inequalities, the entry of transnational capital and the militarization of Mindanao society. While not denying explanatory value to these arguments, this study rejects ethnicity and political economy as dominant causes. It argues that colonial construction of the state and its subsequent transformation from the colonial to the post-colonial period played a determining factor in the shaping of Mindanao's political landscape. The study thus focuses on how local power was shaped by state formation and how the state's ability to establish its authority was mediated by mutual accommodation with strongmen who controlled this frontier zone. An "internal" comparative analysis of two of the island's major provinces, Cotabato and Davao, is employed to show the process of state formation and the shaping of local power from the American colonial period (1900-1941) to the eve of the declaration of martial law by Ferdinand Marcos (1946-72)."--Abstract.
Vita
Photocopy. Ann Arbor, Mich. : UMI Dissertation Services, 1998.
Thesis (Ph.D.)--Cornell University, 1997
Keywords: Electronic books; Central-local government relations -- History -- 20th century -- Philippines; Local government -- History -- 20th century -- Philippines -- Mindanao Island; Islam and state -- History -- 20th century -- Philippines -- Mindanao Island